2003
DOI: 10.1152/ajpheart.01149.2002
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia preserves myocardial function and mitochondrial protein gene expression during hypoxia

Abstract: Hypothermia before and/or during no-flow ischemia promotes cardiac functional recovery and maintains mRNA expression for stress proteins and mitochondrial membrane proteins (MMP) during reperfusion. Adaptation and protection may occur through cold-induced change in anaerobic metabolism. Accordingly, the principal objective of this study was to test the hypothesis that hypothermia preserves myocardial function during hypoxia and reoxygenation. Hypoxic conditions in these experiments were created by reducing O 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 31 publications
3
15
0
Order By: Relevance
“…Temperature preconditioning at 26°C has been shown to reduce calcium‐induced swelling of mitochondria and inhibit an increase in mitochondrial permeability in response to oxidative stress–induced injury 18 . In previous studies at the gene level, hypothermia preserved the signaling for mitochondrial biogenesis as shown by preservation of mRNA levels of biogenesis‐related genes after ischemia–reperfusion injury 29,30 …”
Section: Discussionmentioning
confidence: 98%
“…Temperature preconditioning at 26°C has been shown to reduce calcium‐induced swelling of mitochondria and inhibit an increase in mitochondrial permeability in response to oxidative stress–induced injury 18 . In previous studies at the gene level, hypothermia preserved the signaling for mitochondrial biogenesis as shown by preservation of mRNA levels of biogenesis‐related genes after ischemia–reperfusion injury 29,30 …”
Section: Discussionmentioning
confidence: 98%
“…An intriguing possibility is that mild hypothermia might somehow activate cardioprotective signal transduction pathways. Ning et al75 demonstrated that cold cardioplegia (30°C) preserves mitochondrial protein gene expression during hypoxia, including genes coding for HSP70, ANT 1 , and β-F 1 -ATPase 76. They observed that neither ATP levels nor anaerobic metabolism are linked to mRNA expression of these latter proteins 77.…”
Section: Mechanism Of Cooling-induced Cardioprotectionmentioning
confidence: 99%
“…Oxidative stress to the mitochondria is decreased under hypothermia treatment in cardiomyocyte in vitro study [12]. Hypothermia treatment preserves the prosurvival mitochondria protein genes expression after ischaemic reperfusion injuries [13]. However, the mechanism and effect on mitochondria integrity and energy production under hypothermia treatment remains unclear.…”
Section: Introductionmentioning
confidence: 99%